Seed potatoes the size of a pea - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
African countries, which are producing increasing amounts of potatoes and therefore need to import significant quantities of seed each year, will be interested in potato <<microtubers>>, the size of a pea. These microtubers measure 4-12 mm and weigh...